2020
DOI: 10.1155/2020/3634591
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Anemia among Children Aged 6–59 Months in Ethiopia: Further Analysis of the 2016 Ethiopian Demographic Health Survey

Abstract: Background. Anemia among children is a global public health problem. The burden is high in developing countries including Ethiopia. Although there are some studies about anemia among children, there is a dearth of information about factors associated with anemia in Ethiopia. Therefore, this analysis was performed to identify factors associated with anemia among children aged 6–59 months in Ethiopia. Methods. We used the 2016 Ethiopian Demography and Health Survey (EDHS) data. EDHS was a community-based, cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 31 publications
16
23
0
4
Order By: Relevance
“…had the lowest odds of being anemic. This is consistent with previous studies in Ethiopia (Asresie, Fekadu & Dagnew, 2020). It is possible that as mothers advance in age, they gain experiences with childcare and also, they are more likely to be exposed to education on appropriate practices on childhood nutrition compared with those who are adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…had the lowest odds of being anemic. This is consistent with previous studies in Ethiopia (Asresie, Fekadu & Dagnew, 2020). It is possible that as mothers advance in age, they gain experiences with childcare and also, they are more likely to be exposed to education on appropriate practices on childhood nutrition compared with those who are adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Relatedly, we found that children in large households had higher odds of suffering from anaemia compared to those in small household. This nding con rms a previous study in Ethiopia (Asresie, Fekadu & Dagnew, 2020). Insu cient consumption of appropriate quantity of nutrients due to the high numbers in the households could possibly account for this observation as explained by Asresie, Fekadu and Dagnew, (2020).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study indicated that 48.8% of 6 to 59 months' age children were anemic and with this prevalence, anemia has severe public health significance in the study area. The result is lower than the 2016 Ethiopian Demographic Health Survey (EDHS) report, 57%, 18 further analysis of the 2016 EDHS, 58%, 19 Gondar hospital, 58.6%, 20 Wag-Himra Zone, 66.6%, 21 and Tanzania, 77.2%. 22 The difference in prevalence in different parts of the country might be due to heterogeneity of the studied population, dietary habits, nutritional status, and incidence of worm infestation in defined geographical spots.…”
Section: Discussionmentioning
confidence: 72%
“…This finding confirms a previous study in Ethiopia. 44 Insufficient consumption of appropriate quantity of nutrients due to the high numbers in the households could possibly account for this observation as explained by Asresie et al 44 The study also established that the socioeconomic status (education and wealth) of women had a statistically significant association with childhood anaemia. Specifically, it was found that children whose mothers are in the rich wealth status, as well as those with tertiary level of education, have lower odds of being anaemic.…”
Section: Discussionmentioning
confidence: 88%